Gastrointestinal stromal tumor (GIST) in a female Terrier dog - Yavas, O; Gul Satar, NY; Mutlu, AM; Canatan, U; Özfirat, EC; Akkos, A; Özyiğit, MÖ (Journal of the Hellenic Veterinary Medical Society, 2024)
In this case report, two intestinal masses compatible with gastrointestinal stromal tumor (GIST) is described in a nine-year-old female Terrier dog. The dog presented with complaints of anorexia and vomiting following the ingestion of food. Abdominal ultrasonography revealed two masses in the ventral aspect of the stomach and duodenum. The masses were 6.1×3.7×2.3 cm and 3.2×2×1.7 cm in size, and cut surfaces of the masses were grayish-white-yellow and had a solid appearance. The greater mass invaded the intestinal serosa and mucosa. Cut surfaces were grayish white – yellow and had a solid appearance. Following routine histopathological processing, masses were sectioned at 4 μm, stained with H&E, and immunohistochemically with anti-c-KIT (CD117) antibody. Microscopically, the tumor comprised cells with an oval vesicular nucleus, spindle-shaped eosinophilic cytoplasm and a prominent nucleolus. Mitotic activity was significantly increased (5-6 mitoses at ×400 magnification), and occasionally binucleated cells were observed. Large necrotic areas surrounded by inflammatory cells were noticed. Gastrointestinal stromal tumor is a neoplasm originating from intestinal Cajal cells. The tumor is mostly confused with leiomyoma and leiomyosarcoma; immunohistochemical demonstration of c-KIT is performed for differential diagnosis.